2003
DOI: 10.1046/j.1469-8137.2003.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Does zinc protect the zinc hyperaccumulator Arabidopsis halleri from herbivory by snails?

Abstract: Summary• Hyperaccumulation of metals has been proposed to be a defence against herbivores. Here we investigated whether snails discriminated between plants of Arabidopsis halleri , and the F2 of the cross between A. halleri and A. petraea , on the basis of their internal Zn concentration • A. halleri and F2 plants were grown in four different Zn concentrations. Snails preferred F2 plants to A. halleri plants, and preferred plants that had been grown under low external Zn concentrations, but there was no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
(45 reference statements)
0
29
0
1
Order By: Relevance
“…In laboratory experiments using binary feeding choices, Pollard and Baker (1997), Jhee et al (1999) and Behmer et al (2005) showed that several phytophagous invertebrates preferred to eat low-Zn leaves of the hyperaccumulator Thlaspi caerulescens compared with high-Zn ones. In contrast, Huitson and Macnair (2003) did not Wnd any protective role of Zn in the hyperaccumulator Arabidopsis halleri. Recently, Noret et al (2005) found that organic defences (glucosinolates), rather than Zn, deterred snails from eating the Zn hyperaccumulator T. caerulescens.…”
Section: Introductionmentioning
confidence: 67%
“…In laboratory experiments using binary feeding choices, Pollard and Baker (1997), Jhee et al (1999) and Behmer et al (2005) showed that several phytophagous invertebrates preferred to eat low-Zn leaves of the hyperaccumulator Thlaspi caerulescens compared with high-Zn ones. In contrast, Huitson and Macnair (2003) did not Wnd any protective role of Zn in the hyperaccumulator Arabidopsis halleri. Recently, Noret et al (2005) found that organic defences (glucosinolates), rather than Zn, deterred snails from eating the Zn hyperaccumulator T. caerulescens.…”
Section: Introductionmentioning
confidence: 67%
“…Thus, high-Ni plants were better defended against DBM than low-Ni plants. A critical question for the elemental defence hypothesis (see Huitson and Macnair 2003;Macnair 2003) is whether the defensive effect is due to Ni or to another trait that correlates with hyperaccumulation status. Although we cannot completely rule out other correlated traits (but can address glucosinolate concentrations: see below), our artificial diet experiment did explore the toxicity of Ni to DBM.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the so-called defence hypothesis has been thoroughly investigated. Although some studies showed no defensive effects of high levels of Zn (Huitson and Macnair 2003;Noret et al 2005), a growing body of experimental evidence exists indicating that hyperaccumulation may defend plants against herbivores Martens and Boyd 1994;Pollard and Baker 1997;Jhee et al 1999;Boyd et al 2002;Hanson et al 2003;Behmer et al 2005;Jiang et al 2005;Jhee et al 2006) as well as against pathogens Ghaderian et al 2000;Hanson et al 2003). Defence can be achieved by two known mechanisms.…”
Section: Introductionmentioning
confidence: 99%